Peace of Soul - Sheen, Fulton J. (Fulton John), 1895-1979. (New York : Whittlesey House, 1949)
Written in 1949, Sheen offers in this book a way for man to bring peace to his soul. He asks us to stop blaming our subconscious for all our ills and to examine instead our conscience; to turn away from the psychoanalyst and turn to God. He defines Freudianism as a revolution against the restraining influences of society. He tears the masks from the false gods of rationalized self indulgence and misguided social reform, and explains spiritual discipline and Divine authority as means to greater freedom.
Keywords: Spiritual Theology (3GddGghJ GdQhMjs; Apologetics; Theology